Characteristics of Raindrop Size Distributions during Meiyu Season in Mount Lushan, Eastern China - CHANG, Yi; MA, Qianrong; GUO, Lijun; DUAN, Jing; LI, Jun; ZHANG, Xiaopeng; GUO, Xueliang; LOU, Xiaofeng; CHEN, Baojun (Journal of the Meteorological Society of Japan, 2022)
Meiyu front precipitation makes the region prone to frequent floods, mudslides, landslides, and other disasters and has been the focus of ongoing and challenging meteorological research. Investigation of the Raindrop size distribution (RSD) is essential for exploring the characteristics and underlying physical precipitation processes. In this study, the precipitation characteristics in Lushan mountainous areas during the Meiyu season were investigated using laser disdrometer observed RSD data from 2016 to 2020. For the average spectra of five rain rate classes, the concentrations of large raindrops (> 0.5 mm) increased with rain rate (R), whereas the concentrations of small raindrops (< 0.5 mm) increased only under rain rates higher than 10 mm h−1. The gamma distribution parameters of N0 (intercept parameter) and Λ (slope parameter) increased/decreased with rain rate, and the shape parameter µ exhibited negative values in different rain rate classes. The distribution pattern features were N(D) =721D−1.79e−1.20D. Distributions of the frequency for mass-weighted mean diameter (Dm) and the logarithm of the generalized intercept parameter (log10 Nw) both showed a unique bimodal type, and an exceptionally high Nw (log10Nw > 4.5) subset with small Dm was determined. The stratiform and convective rains of RSD were also investigated. Dm–R and Nw–R showed similar variations in two types of precipitation. The lower µ values resulted in higher primary and constant coefficients in the quadratic polynomial fitting for the µ–Λ relationship (Λ = 0.0347µ2 + 1.180µ + 2.495). The Z–R relationship (Z for radar reflectivity factor) in stratiform precipitation characteristics was Z = 203R1.59. Further investigations showed that high Nw values usually occurred in persistent precipitation. The RSD can be characterized as high concentrations of the first two diameter classes with a narrow spectrum width (< 1 mm), which were captured during in-cloud rain with a low but continuous rain rate (< 5 mm h−1). The mountainous topography plays an important role in reshaping the characteristics of RSD and physical processes of precipitation.